ChemInform Abstract: Reaction of Alkynes and Azides: Not Triazoles Through Copper—Acetylides but Oxazoles Through Copper—Nitrene Intermediates. Issue 39 (23rd September 2014) - Haldon, Estela; Besora, Maria; Cano, Israel; Cambeiro, Xacobe C.; Pericas, Miquel A.; Maseras, Feliu; Nicasio, M. Carmen; Perez, Pedro J.
Abstract Two copper complexes for the regioselective formation of 2, 5‐disubstituted oxazoles from carbonyl azides and terminal alkynes are developed.